CI:99-00 - Carnegie International 1999-2000 : Artists' Reader. - Carnegie International 1999-2000, Pittsburgh; Ballard, J.C.; Ballard, J.G.; Benthum, Jeremy; Bergier, Jacques; Borges, Jorge Luis, 1899-1986.; Calvino, Italo; Carson, Anne; Carver, Raymond; Donne, John; Epstein, Mark; Genet, Jean; et al. (Pittsburgh : Carnegie Museum of Art, 1999)
Ackermann, Franz ; Barney, Matthew ; Cardiff, Janet ; Chen Zhen ; Currin, John ; Darboven, Hanne ; Demand, Thomas ; Dion, Mark ; Doherty, Willie ; Eliasson, Olafur ; Geers, Kendell ; Gonzalez-Torres, Felix ; Hamilton, Ann ; Hernández-Diez, José Antonio ; Huyghe, Pierre ; Katz, Alex ; Kentridge, William ; Kingelez, Bodys Isek ; Kinoshita, Suchan ; Kippenberger, Martin ; Marshall, Kerry James ; Murakami, Takashi ; Neshat, Shirin ; Neto, Ernesto ; Ofili, Chris ; Orozco, Gabriel ; Othová, Markéta ; Owens, Laura ; Ruscha, Edward ; Schneider, Gregor ; Sidén, Ann-Sofi ; Signer, Roman ; Sze, Sarah ; Taylor-Wood, Sam ; Tevet, Nahum ; Thater, Diana ; Tuymans, Luc ; Walker, Kara ; Wall, Jeff ; Wilson, Jane & Louise
Engels
Carnegie International 1999-2000, Carnegie Museum of Art, Pittsburgh, Nov 6, 1999 - Mar 26, 2000
boek